HOMEWORK MANAGEMENT IN ACADEMIC LEARNING - Ecaterina Sarah FRĂSINEANU (Universitaria Publishing House, Craiova, 2023)
The article promotes the concept of rationalization or optimized perspective of the construction/ assignment of homework by the teachers and their approach by the students, so that the practice of certain tasks and the accomplishment of certain applied works could be integrated as well as possible into the educational process. The knowledge of the students' insights regarding the motivation associated with solving homework, difficulties, the relationship amount-difficulty-time and allocated effort, represents a type of feedback necessary both for the students, for a more sustained involvement in the management of the learning resources, but also for the teachers, for a better adjustment of their actions. Because they were asked to professionally reflect specifically on meeting these conditions and were supported in capitalizing on self-management strategies, our intention was to find out whether students of the psychopedagogical training program for the teaching profession improve their commitment and satisfaction in completing homework. Their responses showed us that effectiveness can be achieved by initiating/ triggering the moment homework is to be done, eliminating procrastination, by identifying the time and context in which allotting homework is useful, by taking a strategic approach, during which distractors were liminated and the necessary materials were provided. When solving homework independently, students should optimally use their resources, combine solving moments with some breaks, review the solutions globally, pay attention to respecting the submission deadlines, and capitalize on the external strengths and recommendations in the presentation of the results.